STRUCTURAL INTEGRITY ASSESSMENT OF LPG-FIRED CABINET DRYER USING FINITE ELEMENT ANALYSIS (FEA) - Nafisah Amalia; Yusi Amalia Renaningtyas; Apriandi MS, Nanang; Yusuf Dewantoro Herlambang; Avicenna An-Nizhami; Padang Yanuar; Aris Fiatno (Journal of Mechanical Engineering and Applied Technology, 2025)
Cabinet-type dryers powered by Liquefied Petroleum Gas (LPG) are widely recognized as an efficient drying solution, particularly for small and medium-sized industries. However, the structural strength and durability aspects of these dryers often receive insufficient attention, although they operate under a combination of static and thermal loads that may potentially trigger structural failure. This study aims to evaluate the structural strength of a cabinet-type LPG dryer using the Finite Element Analysis (FEA) method by considering variations in operating temperature and constant mechanical loading. Simulations were conducted within an operating temperature range of 48.049°C to 75.767°C under a constant load of 40 kg. The key parameters analyzed include total deformation, stress distribution, and structural safety factor. The results revealed a maximum deformation of 1.094 mm and a peak stress of 1030.7 MPa concentrated in the plenum chamber area, identified as a critical zone due to the combined effects of thermal and mechanical loading. The maximum safety factor reached 15, while the minimum value of 0.24255 indicates the need for localized design improvements in certain regions. These findings demonstrate the effectiveness of FEA in predicting the structural response of drying equipment and provide a scientific foundation for enhancing structural safety and reliability. Further studies are recommended to integrate coupled thermal-structural analysis and experimental validation to improve the accuracy of the results. Keywords: cabinet dryer; finite element analysis (FEA); safety factor; structural analysis; temperature distribution